A cross-layer approach for multi-layer multicast routing in multi-channel multi-radio wireless mesh networks. (2016) - Farzinvash, Leili; Dehghan, Mehdi
In this paper, we consider multicast applications with bandwidth heterogeneous receivers in multi-channel multi-radio wireless mesh networks (MC-MR WMNs). Multi-layering is a well-established approach to handle bandwidth heterogeneity of the receivers. Existing multi-layering schemes have addressed only single-channel settings. In the context of MC-MR WMNs, the channel assignment problem is coupled with multicast routing, thus necessitating a cross-layer solution. In this paper, we propose an optimal cross-layer model, which aims at maximising the total number of obtained layers by the receivers. We include network coding in our design to take advantage of its capacity boosting in multicasting. To alleviate time complexity of the optimal model, we propose grouping-based multi-layer multicast (GMLMC) algorithm, which yields close to optimal throughput, i.e., nearly 96% of the optimum, in polynomial time. Moreover, the pattern of layer reception to the receivers in the outcomes of GMLMC resembles very much to the optimal results.